2015
DOI: 10.1007/s11146-015-9537-9
|View full text |Cite
|
Sign up to set email alerts
|

Housing Wealth, Financial Wealth and Consumption Expenditure: The Role of Consumer Confidence

Abstract: The objective of this paper is to examine the role of consumer confidence on the relationship between two forms of wealth-housing and financial-and four categories of consumption expenditure, which include total consumption, service, durable goods and nondurable goods consumption. This paper uses U.S. quarterly data from 1978 to 2012 for its analysis. Applying the FMOLS estimation method, the results show that consumer confidence has a positive effect on the association between housing wealth and consumption e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 49 publications
0
12
0
1
Order By: Relevance
“…With an average higher salary, the community tends to spend more for their needs (Ulf, 2019). Fereidouni & Tajaddin (2015) conducted a study on consumption expenditure and its correlation with wealth. They found that people with higher income will also have higher consumption spending.…”
Section: Figure 5 Types Of Influencersmentioning
confidence: 99%
“…With an average higher salary, the community tends to spend more for their needs (Ulf, 2019). Fereidouni & Tajaddin (2015) conducted a study on consumption expenditure and its correlation with wealth. They found that people with higher income will also have higher consumption spending.…”
Section: Figure 5 Types Of Influencersmentioning
confidence: 99%
“…However, as for the housing wealth effect, this will only benefit homeowners, while those who rent housing or families hoping to improve their housing will suffer from the effect. In regions with a high homeownership rate, the housing wealth effect will be more significant (Aladangady, 2017;Attanasio et al, 2009;Campbell & Cocco, 2007;Carrol et al, 2011;Case et al, 2005;Chen et al, 2010Chen et al, , 2018Cooper & Dynan, 2016;Dvornak & Kohler, 2007;Elbourne, 2008;Fereidouni & Tajaddini, 2017;Gan, 2010;Iacoviello & Neri, 2010;Muellbauer & Murphy, 2008;Paiella & Pistaferri, 2017;Simo-Kengne et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, from previous studies, in a region with high rates of homeownership and low loan interest rates, under the hypothesis of a housing wealth effect 3 , changes in housing prices should exert an influence on consumption expenditure, which will then further influence the performance of the economy. The reason is that housing by its sheltering nature generates personal expenditure 4 that directly and indirectly contributes towards the categories of consumption (Aladangady, 2017;Angrisani et al, 2019;Attanasio et al, 2009;Campbell & Cocco, 2007;Carrol et al, 2011;Case et al, 2005;Chen et al, 2010Chen et al, , 2018Cooper & Dynan, 2016;Dvornak & Kohler, 2007;Elbourne, 2008;Fereidouni & Tajaddini, 2017;Gan, 2010;Iacoviello & Neri, 2010;Muellbauer & Murphy, 2008;Paiella & Pistaferri, 2017;Simo-Kengne et al, 2013). As consumption is one of the main components in the formula for gross domestic product (GDP) 5 , it is considered that the impact of a housing wealth effect on consumption suggests that there exists a strong positive link between the housing market and macroeconomic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the economic research field has begun to attach importance to consumers' subjective feelings and consumer confidence (Ahmad & Rangaraju, ; Çelik, ; Gausden, Hasan, Economics, & Phillips, ; Johnson & Naka, ; Nyman & Ormerod, ). Research on consumer psychology showed that consumers' subjective confidence of economic condition would directly predict and influence macroeconomic condition, along with the concept of Consumer Confidence Index (CCI) emerging (Gholipour Fereidouni & Tajaddini, ; Li, Chang, & Chen, ; Sorić, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the economic research field has begun to attach importance to consumers' subjective feelings and consumer confidence (Ahmad & Rangaraju, 2017;Çelik, 2016;Gausden, Hasan, Economics, & Phillips, 2017;Johnson & Naka, 2014;Nyman & Ormerod, 2014). Research on consumer psychology showed that consumers' subjective confidence of economic condition would directly predict and influence macroeconomic condition, along with the concept of Consumer Confidence Index (CCI) emerging (Gholipour Fereidouni & Tajaddini, 2017;Li, Chang, & Chen, 2008;Sori c, 2018). CCI, also known as Index of Consumer Sentiment, is used to reflect the consumers' psychological feelings and confidence about economic situation and consumption at the moment or in a certain period of time (Islam & Mumtaz, 2016;Kłopocka, 2017) ICE represents the level of consumers' expectation of the economic condition and consumption over a period in the future, which reflects the confidence of future economic development.…”
Section: Introductionmentioning
confidence: 99%